On the Joint Effects of Stimulus Quality and Word Frequency in Lexical Decision: Conditions That Promote Staged Versus Cascaded Processing. - Besner, Derek; Young, Torin (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2022)
Additive effects of Stimulus Quality and Word Frequency on RT in the context of lexical decision when the foils are orthographically legal were first reported more than 4 decades ago, and subsequently replicated numerous times. Two accounts are considered that make different a priori predictions when the foils are orthographically illegal. Yap and Balota's (2007) Familiarity Discrimination account predicts additive effects of these two factors on mean RT and across the RT distribution because it assumes a staged normalization process that deals with the effect of low Stimulus Quality; a subsequent process produces the effect of Word Frequency. In contrast, O'Malley and Besner's (2008) context-dependent thresholding/cascading account predicts an interaction because the use of illegal foils eliminates the need for thresholding at the letter level normally used to protect against lexical capture (identifying a nonword as a word) in experiments where Stimulus Quality is a factor, and hence the system reverts to processes in cascade. Critically, the present experiment yielded an interaction in which low-frequency words were more impaired by low Stimulus Quality than were high-frequency words. These data are inconsistent with the Familiarity Discrimination account as currently constituted, but consistent with a context-specific cascaded account. Further discussion considers how the Familiarity account may be modified so as to accommodate these data. Most generally, these data add to the view that processing is highly malleable (context dependent) rather than the received view, especially in regard to computational accounts, in which interactive-activation dynamics dominate.